Pengelolaan Wilayah Pesisir Berbasis Pengurangan Risiko Bencana Gempabumi dan Tsunami di Kabupaten Kulon Progo Daerah Istimewa Yogyakarta - Despry Nur Annisa; Djati Mardiatno; Dyah Rahmawati Hizbaron (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
This study discussed about management of coastal area in Kulon Progo Regency based on the risk of the earthquake and tsunami. The aim of this study was to identify potential hazard earthquake and tsunami, analyze the suitability of using land exists to spatial pattern planning, and describe direction of management area’s coastal based on reduction of earthquake and tsunami risk in Kulon Progo Regency. Data was used in this study was information about earthquake and tsunami occurrence obtained from the government institution and also United States Geological Survey (USGS), satelite imagary from digital globe. Data of spatial policy which was used in this study were document of Area Spatial Planing, Coastal Zoning Plan, and small islands at study site. Analyzer used in this study were spatial analyzis, peak ground acceleration analyzis, cross tabulation, and descriptive-qualitative. The result of this study showed that coastal’s area in Kulon Progo Regency categorized as having a medium earthquake with PGA value 134, 754 gal and a high tsunami potential with an area of 7702, 614 Ha. The results of the assessment of the conformity of existing land use in 2016 to the spatial plan in the document of Coastal Zoning Plan of Kulon Progo Regency in 2014-2034 tends to show high deviation of space with the extent of using land mismatch of 10399,139 Ha of the total area of research. Based on that, the direction of coastal management of Kulon Progo Regency has five management scenarios, namely; (1) scenario a-1 in the form of early warning and direction of high population density; (2) b-I scenario in the form of early warning, mitigation, and direction of high population density; (3) b-II scenario in the form of warning, mitigation, and direction of medium population density; (4) b-III scenario in the form of early warning, mitigation, and low population density direction; and (5) scenario c-III in the form of early warning, mitigation, preparedness and low population density directive.